Genome-wide association studies in pediatric chronic kidney disease - Gupta, Jayanta; Kanetsky, Peter A.; Wuttke, Matthias; Köttgen, Anna; Schaefer, Franz; Wong, Craig S. (Pediatric nephrology, 2016)
The genome-wide association study (GWAS) has become an established scientific method that provides an unbiased screen for genetic loci potentially associated with phenotypes of clinical interest such as chronic kidney disease (CKD). Thus, GWAS provides opportunities to gain new perspectives regarding the genetic architecture of CKD progression by identifying new candidate genes and targets for intervention. Thus it has become an important arm of translational science providing a complementary line of investigation to identify novel therapeutics to treat CKD. In this review, we describe the method and the challenges of performing GWAS in the pediatric CKD population. We also provide an overview of successful GWAS for kidney disease, and we discuss the established pediatric CKD cohorts in North America and Europe that are poised to identify genetic risk variants associated with CKD progression.
21 October 2015
Gesehen am 28.08.2020